Modified French Osteotomy for Humeroradial Synostosis in a Child with Multiple Synostoses Syndrome: A Case Report - Haniza, Binti Sahdi; Ahmad Hata, Bin Rasit; Khoo, C. S; Agusmanan, Bin Bojeng; Nur-Alyana, B. A. (Malaysian Orthopaedic Association (MOA), 2019)
Congenital humeroradial synostosis can occur as an isolated clinical entity or as part of a syndrome. Bilateral elbow fixed flexion deformity is very incapacitating and challenging to treat. Here we present the case of a boy with fixed flexion deformity of both elbows due bilateral humeroradial synostosis. Other characteristic features of multiple synostoses syndrome were also present in this child, his elder brother and mother. We elected to improve the position of the right elbow by adapting the modified French osteotomy described by Bellemore et al.